Effect of Noradrenaline on the Facial Stimulation-Evoked Mossy Fiber-Granule Cell Synaptic Transmission in Mouse Cerebellar Cortex - Li, Bing-Xue; Jin, Hua; Zhang, Guang-Jian; Cui, Li-Na; Chu, Chun-Ping; Qiu, De-Lai (Frontiers in Neuroscience, 2021)
Noradrenaline is an important neuromodulator in the cerebellum. We previously found that noradrenaline depressed cerebellar Purkinje cell activity and climbing fiber–Purkinje cell synaptic transmission in vivo in mice. In this study, we investigated the effect of noradrenaline on the facial stimulation-evoked cerebellar cortical mossy fiber–granule cell synaptic transmission in urethane-anesthetized mice. In the presence of a γ-aminobutyrateA (GABAA) receptor antagonist, air-puff stimulation of the ipsilateral whisker pad evoked mossy fiber–granule cell synaptic transmission in the cerebellar granular layer, which expressed stimulus onset response, N1 and stimulus offset response, N2. Cerebellar surface perfusion of 25 μM noradrenaline induced decreases in the amplitude and area under the curve of N1 and N2, accompanied by an increase in the N2/N1 ratio. In the presence of a GABAA receptor blocker, noradrenaline induced a concentration-dependent decrease in the amplitude of N1, with a half-maximal inhibitory concentration of 25.45 μM. The noradrenaline-induced depression of the facial stimulation-evoked mossy fiber–granule cell synaptic transmission was reversed by additional application of an alpha-adrenergic receptor antagonist or an alpha-2 adrenergic receptor antagonist, but not by a beta-adrenergic receptor antagonist or an alpha-1 adrenergic receptor antagonist. Moreover, application of an alpha-2 adrenergic receptor agonist, UK14304, significantly decreased the synaptic response and prevented the noradrenaline-induced depression. Our results indicate that noradrenaline depresses facial stimulation-evoked mossy fiber–granule cell synaptic transmission via the alpha-2 adrenergic receptor in vivo in mice, suggesting that noradrenaline regulates sensory information integration and synaptic transmission in the cerebellar cortical granular layer.